Predicting Consanguinity Rates from Exome Sequencing Data in the Lebanese Population - Hanna, Eileen Marie; Mehawej, Cybel; Assy, Joelle; Corbani, Sandra; Korban, Rima; Megarbane, Andre; Chouery, Eliane (The Journal of molecular diagnostics : JMD, 2025)
Consanguinity, prevalent in certain populations because of cultural and social factors, significantly increases the risk of genetic autosomal recessive disorders. In Lebanon, consanguineous marriages constitute 35.5% of unions, with first cousin marriages being the most common. This study aims to develop a model to predict consanguinity status using total runs of homozygosity (ROH) size derived from exome sequencing data. In this study, a cohort of 784 Lebanese individuals was analyzed, with consanguinity labels assigned based on pedigree information. ROHs were detected from exome sequencing data using AutoMap. The analysis focused on 521 subjects for whom the consanguinity or nonconsanguinity label was clearly determined, leading to the development of two logistic regression models: one including outliers (accuracy, 91%) and one excluding them (accuracy, 94%). The second model established specific ROH thresholds for categorizing consanguinity: nonconsanguineous [<40.28 megabases (Mb)], uncertain (40.28 to 79.17 Mb), probable consanguinity (79.18 to 118.06 Mb), and consanguineous (>118.06 Mb). This study provides a valuable tool for clinical genetics in populations with high consanguinity rates, offering insights into the genetic risks associated with consanguinity and aiding in the identification and counseling of affected individuals. Moreover, the current findings underline the importance of population-specific thresholds in accurately assessing consanguinity status.